Cataract Prevalence and Risk Factors Among Type 2 Diabetics in Derna Teaching Hospital - Abeer AL-Mansori; Naeima Elzlitni (AlQalam Journal of Medical and Applied Sciences, 2024)
This study aimed to assess the prevalence of cataracts among type 2 diabetic patients attending the ophthalmology department at Derna Hospital and to identify key diabetic risk factors associated with cataract development. A hospital-based case-control study was conducted from 2 November 2023 to 27 February 2024 at Alwahda Teaching Hospital in Derna City. Among 220 type 2 diabetic patients attending the ophthalmology department during this period, approximately 180 were diagnosed with cataracts. Participants provided consent for participation, and those with cataracts due to reasons other than diabetes were excluded. Data were collected through face-to-face interviews using a multidata questionnaire, followed by comprehensive eye examinations and relevant tests. Risk factors including sex, age, duration of diabetes, fasting blood sugar, and hypertension were compared between patients with and without cataracts. Statistical analysis was performed using percentages, proportions, and the Chi-square test. The results showed that gender and smoking were not significantly associated with cataract incidence (p > 0.05), but age, duration of diabetes, HbA1c levels, hypertension, and fasting blood sugar were significantly higher in the cataract group (p < 0.05). Multiple regression analysis indicated that the duration of diabetes was significantly correlated with the presence of cataracts (p < 0.05). In conclusion, the duration of diabetes was identified as the most significant risk factor for cataracts in diabetic patients, highlighting the importance of cataract screening programs for diabetic patients to prevent visual impairment and related disabilities. تهدف هذه الدراسة إلى تقييم انتشار السَاد بين مرضى السكري من النوع الثاني الذين يراجعون قسم طب العيون في مستشفى درنة، وتحديد عوامل الخطر الرئيسية المرتبطة بتطور السَاد. تم إجراء الدراسة مقارنة حالة في مستشفى من 2 نوفمبر 2023 إلى 27 فبراير 2024 في مستشفى الوحدة التعليمي في مدينة درنة. من بين 220 مريضًا من مرضى السكري من النوع الثاني الذين راجعوا قسم العيون خلال هذه الفترة، تم تشخيص حوالي 180 منهم بإصابات بالساد. قدم المشاركون موافقتهم للمشاركة، وتم استبعاد من يعانون من الساد بسبب أسباب أخرى غير مرض السكري. تم جمع البيانات من خلال المقابلات المباشرة باستخدام استبيان متعدد البيانات، تلاها فحوصات شاملة للعين والاختبارات ذات الصلة. تم مقارنة عوامل الخطر بما في ذلك الجنس، العمر، مدة مرض السكري، مستوى السكر في الدم الصائم، وارتفاع ضغط الدم بين المرضى المصابين بالساد وغير المصابين به. تم إجراء التحليل الإحصائي باستخدام النسب المئوية، والنسب، واختبار كاي تربيع. أظهرت النتائج أن الجنس والتدخين لم يكونا مرتبطين بشكل كبير بحدوث السَاد (p > 0.05)، ولكن العمر، مدة السكري، مستويات السكر التراكمي، ارتفاع ضغط الدم، ومستوى السكر في الدم الصائم كانت أعلى بشكل كبير في مجموعة المصابين بالساد (p < 0.05). أشار تحليل الانحدار المتعدد إلى أن مدة مرض السكري كانت مرتبطة بشكل كبير بوجود السَاد (p < 0.05). في الختام، تم تحديد مدة مرض السكري كأهم عامل خطر للسَاد لدى المرضى السكريين، مما يبرز أهمية برامج فحص السَاد لمرضى السكري لمنع تدهور الرؤية والإعاقات ذات الصلة